1993
DOI: 10.1002/eji.1830230911
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor production by rat mast cells

Abstract: Leukemia inhibitory factor (LIF) is a pluripotent cytokine of importance in the regulation of immune and inflammatory responses. This cytokine may play an important role in neuronal development and bone metabolism. We have examined the ability of freshly isolated rat mast cells and mast cell lines to produce LIF at both the mRNA and bioactivity levels. Initial experiments demonstrated that two mucosal mast cell-like cell lines RBL.2H3 and RCMC9 endogenously produced low levels of LIF bioactivity. The productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Although we have identified LIF as a keratinocyte‐derived mast cell growth‐enhancing factor [8], LIF is also produced from activated mast cells [26]. Mast cells, thus, may regulate their proliferation by themselves through the secretion of LIF.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have identified LIF as a keratinocyte‐derived mast cell growth‐enhancing factor [8], LIF is also produced from activated mast cells [26]. Mast cells, thus, may regulate their proliferation by themselves through the secretion of LIF.…”
Section: Discussionmentioning
confidence: 99%
“…Other mast cell cytokine responses, including the production of IL-3 and GM-CSF, have been shown to be regulated at a posttranscriptional level (42), and our results may reflect a similar mechanism. In previous studies we have observed high levels of IL-6 mRNA expression after calcium ionophore (A23187) treatment under conditions that have not led to IL-6 expression at the protein level (7,43). Extensive previous studies have failed to demonstrate detectable levels of cell-associated IL-6 in rat PMC under any culture conditions, although recombinant IL-6 added to cell pellet preparations can be readily detected in "spiking" experiments (7).…”
Section: Discussionmentioning
confidence: 99%
“…In airway tissue, fibronectin is produced by epithelial and mesenchymal cells and is an important signal protein involved in the proliferation, migration and attachment of cells at sites of injury and inflammation (Rickard et al , 1993). LIF is also produced by mast cells isolated from the rat (Marshall et al , 1993). Given the proximity of mast cells to sensory nerves (Marshall & Waserman, 1995) and the epithelium (Lamb & Lumsden, 1982), the ability of mast cells to produce LIF may also be an important factor in the proliferative response following mucosal damage.…”
Section: Discussionmentioning
confidence: 99%